Application of Machine Learning in Survival Analysis - Kutukov, Nikolay; Zimmermann, Pavel, 1980-; Štěpánek, Lubomír; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This bachelor thesis focuses on the application of machine learning algorithms in the domain of survival analysis. The aim is to conduct a comparative analysis between classical survival analysis approaches and modern machine learning algorithms, assessing their performance and interpretability.
Vedoucí práce: Pavel Zimmermann
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: data analytics [obor bakal. práce]; bakalářské práce; bachelor's theses